Developing an e-module of making Edmodo-based Hosanna Moda system bustier to improve learning independence and learning achievement - Lestari Rochmatun Choirunnisya'; Putu Sudira (Jurnal Pendidikan Vokasi, 2021)
This study aims to: 1.) Develop an Edmodo-based e-module for making  Hosanna Moda system bustier to increase independence and achievement in learning custom-made clothing; 2.) Describe the feasibility of the developed  e-module; and 3.) Reveal the effectiveness of the developed e-module in increasing student learning independence and learning achievement. This research is development research, which was carried out on grade XII students of Fashion, State Vocational High School 3 Magelang. The product trial consisted of a validity test by three experts, a small-scale trial involving 12 students, a large-scale trial involving 24 students, and an effectiveness test involving one control and one experimental group each consisting of 36 students. The data were collected using questionnaires and tests as well as through interviews. The data analysis used is a quantitative description and the effectiveness testing using the t-test. The results of the study are as follows: 1.) The developed e-module contains learning materials about making the Hosanna Moda system bustier illustrated with relevant pictures to make it easier for students to understand it when studying independently; 2.) The product has been declared feasible by a material expert, media expert, and linguist. In the operational trial, teacher responses are with an average score of 5.00 (very good category and suitable for use), and student responses are with an average score of 4.59 (very good category and suitable for use); and 3.) The results of the effectiveness testing on student learning independence is at the significance level of 0.000 (<0.050) indicating that the learning independence of experimental group students was higher than that of the control group, while the results of the effectiveness test on student learning achievement are at the significance level of 0.001 (<0.050) indicating an average value. The posttest average score of the experimental group was much higher than that of the control group. Thus, it can be concluded that the developed e-module is effective in increasing student learning independence and learning achievement.